2012
DOI: 10.1080/02786826.2011.602761
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of Gas–Particle Partitioning of Primary Organic Aerosol Emissions from a Small Diesel Engine

Abstract: A new experimental technique has been developed to study the gas-particle partitioning behavior of primary organic aerosol (POA) emissions from combustion sources at atmospherically relevant concentrations. The technique involves slowly filling a Teflon chamber with a constant emission source. As aerosol concentrations increase inside the chamber, the gas-particle partitioning of semivolatile organics shifts to the particle phase, thus increasing the fuel-based POA emission factor. The technique allows charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 48 publications
2
58
0
Order By: Relevance
“…At equilibrium, the volatility of organic species (saturation vapor pressure or, equivalently, saturation concentration, C * ) dictates gas-particle partitioning (Donahue et al, 2006). Enthalpies of vaporization ( H vap ) also influence the change in partitioning with temperature (Epstein et al, 2010;Ranjan et al, 2012). Depending on the volatility of POA and atmospheric perturbations (dilution, changing temperature), semi-volatile species in POA will dynamically partition into gas or particle phases as they move downwind.…”
Section: Introductionmentioning
confidence: 99%
“…At equilibrium, the volatility of organic species (saturation vapor pressure or, equivalently, saturation concentration, C * ) dictates gas-particle partitioning (Donahue et al, 2006). Enthalpies of vaporization ( H vap ) also influence the change in partitioning with temperature (Epstein et al, 2010;Ranjan et al, 2012). Depending on the volatility of POA and atmospheric perturbations (dilution, changing temperature), semi-volatile species in POA will dynamically partition into gas or particle phases as they move downwind.…”
Section: Introductionmentioning
confidence: 99%
“…γe is often assumed to be in unity in fitting TD data (Grieshop et al, 2009;Li et al, 2016); however, recent 25 studies reported a γe values between 0.01 and 1 for different aerosol systems (Cappa and Jimenez, 2010;Saha et al, 2017b;Saha and Grieshop, 2016;Saleh et al, 2013). Similarly, in literature, different ranges of ΔHvap values are reported for different aerosol systems (Epstein et al, 2010;May et al, 2013c;Ranjan et al, 2012). TD data collected at varying (T, Rt) provides additional constraints on feasible γe and ΔHvap values (Saha et al, 2015(Saha et al, , 2017bSaha and Grieshop, 2016).…”
Section: Parameterizing Volatilitymentioning
confidence: 99%
“…An analysis of temperature effects on the partitioning of semi-volatile materials from vehicular emissions (see Figure S5) indicates that while 40-70% of semi-volatile emissions reside in the particle-phase under typical winter conditions (0-10°C), only 10-20% do so under summer conditions (20-30°C). This analysis used the gasoline POA volatility distribution from May et al (2013a) and ΔHvap from Ranjan et al (2012) and considered a range of OA concentrations for a typical roadside environment (e.g., 0.5 to 5 µg m -3 ). Second, the 10 difference could be due inter-seasonal differences in emission properties (the volatility of what is emitted) and atmospheric dilution.…”
Section: Observed Evaporations In Td With Downwind Distancementioning
confidence: 99%
See 1 more Smart Citation
“…This has been accomplished with dilution samplers , thermodenuders (Huffman et al 2008;Huffman et al 2009), and smog chambers (Grieshop et al 2007;Ranjan et al 2012). The data are then fit into VBS model using absorptive partitioning theory to determine the volatility distribution and particle fractions.…”
Section: Effect Of Temperature Dependence and Dilutionmentioning
confidence: 99%